A laser cooling scheme for precision measurements using fermionic barium monofluoride (137Ba19F) molecules. (7th September 2021) - Kogel, Felix; Rockenhäuser, Marian; Albrecht, Ralf; Langen, Tim
Abstract: We theoretically investigate the laser cooling of fermionic barium monofluoride ( 137 BaF) molecules, which are promising candidates for precision studies of weak parity violation and nuclear anapole moments. This molecular species features two nuclear spins, resulting in a hyperfine structure that is considerably more complicated than the one found in the usual laser-cooled diatomics. We use optical Bloch equations and rate equations to show that optical cycling, sub-Doppler cooling and bichromatic forces can all be realized under realistically achievable experimental conditions.